Dampak Literasi Keuangan, Sikap Keuangan dan Ingklusi Keuangan Terhadap Kinerja UMKM Di Kabupaten Sumbawa - Suryani, Hanifa Sri (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The efficacy of Micro, Small, and Medium Enterprises (MSMEs) is crucial to a nation's economy, particularly in emerging nations such as Indonesia. Micro, small, and medium enterprises (MSMEs) not only provide substantial contributions to gross domestic product (GDP) but also serve as the primary source of employment, capable of accommodating a considerable workforce. Due to their flexibility, MSMEs can swiftly adjust to market fluctuations and consumer demands, thereby serving as a catalyst for innovation and local economic development. This study aimed to examine the impact of financial literacy, financial attitudes, and financial inclusion on the performance of small and medium enterprises (MSMEs) in Sumbawa Regency. This research used a quantitative methodology using a population of 1,362 MSME participants in Sumbawa Regency. The employed sampling approach is total sampling, with the sample size calculated using the Slovin formula, resulting in 100 respondents. Data collection was conducted using a questionnaire including a Likert scale ranging from 1 to 4. Data analysis was conducted via Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The study's findings indicate that financial literacy, financial attitudes, and financial inclusion positively and significantly impact MSME performance in Sumbawa Regency.